Return-to-Play criteria following lower limb muscle injuries in soccer: A systematic review with evidence synthesis - Pecci, J.; Van Dyk, N.; Myer, G. D.; Sañudo, B. (Sports Medicine, 2026)
Objective The objective was to systematically identify and categorize return-to-play (RTP) domains and criteria used following muscle injuries in male soccer players, and to describe the certainty of the evidence according to the number, design and methodological quality of the studies implementing RTP criteria within each domain. Methods In total, six databases were searched up to 10 March 2024. Studies reporting RTP criteria for hamstring, adductor, quadriceps, and calf injuries, as well as general criteria for all muscle injuries, were included. The certainty of evidence for RTP criteria was assessed on the basis of the studies citing each criterion. Results Out of 58,057 records, 135 studies met the inclusion criteria. Strength and pain criteria are the most cited tests for determining RTP clearance following hamstring injuries, particularly criteria related to between-limb knee flexors/extensors strength symmetry and no pain during soccer-specific actions. Range of motion criteria (active knee extension, passive and active straight leg raise, and Askling-H tests) and subjective readiness demonstrated the highest certainty of evidence in RTP decision making after hamstring injuries. RTP criteria following adductor injuries showed a moderate-to-very-low certainty of evidence across domains. Criteria for quadriceps and calf injuries ranged from low to very low evidence, while general lower limb muscle injury criteria had only very low evidence. Following adductor injuries, the highest evidence (moderate) was shown by pain assessments and completing at least one full team training session. Conclusions Symmetry between limbs in knee flexor and extensor strength combined with no pain during soccer-specific actions were the most frequently implemented RTP criteria for hamstring injuries. In addition, range of motion evaluation (i.e., active knee extension, passive and active straight leg raise, and Askling- H tests) and subjective readiness assessments have been more consistently employed in higher-quality intervention studies than other domains following hamstring injuries in soccer players. Pain assessments, completing at least one full team training session and restoring strength levels are the most cited criteria for RTP following adductor injuries. The evidence base describing RTP criteria for quadriceps and calf injuries is limited and is not implemented in randomized controlled trials with high methodological quality, highlighting the need for further robust research in these domains.